Studies on the toxicity, metabolism, and antichminesmrase properties of acephate and methamidophos - Hussain, M.A. (Informa UK Limited, 1985)
The toxicity of acephate to four species of aquatic insects, as well as the metabolism and cholinesterase-inhibiting properties of the chemical in the rat were studied. The results indicated that mayfly larvae were very sensitive to the toxic effects of acephate, whereas larvae of the stonefly, damselfly and mosquito were much less sensitive. In the rat, orally-administered acephate was rapidly absorbed from the intestines and severely inhibited the chclinesterases in the blood and brain. The enzymes began to recover after 24 hours, while the chemical was completely eliminated within three days. The amount of methamidophos observed in the liver was extremely low. The cholinesterase-inhibiting properties of acephate and methamidophos were compared in vitro to that of paraoxon, a known strong anticholinesterase. Enzymes from four vertebrates were used. In all cases, except one, acephate was found to be six orders of magnitude weaker than paraoxon, whereas methamidophos was three orders weaker. Trout brain cholinesterase was the exception; it was as sensitive to paraoxon as it was to methamidophos. Finally, four cholinesterases were inhibited with methamidophos, and their ability to reactivate spontaneously or to recover by induction with pyridine aldoxime methiodide (PAM) in vitro were determined. The results suggested that methamidophos-inhibited cholinesterases did not reactivate spontaneously; instead the enzymes remained inhibited either in a phosphorylated or an aged state. The significance of these results are discussed in relation to the use of acephate for forest insect pests.